2020
DOI: 10.3390/agronomy10101452
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Organic and Mineral Fertilization on Soil Enzyme Activities and Bacterial Community in the Below- and Above-Ground Parts of Wheat

Abstract: Bacterial community and soil enzymatic activity depend on soil and management conditions. Fertilization is an important approach to maintain and enhance enzyme activities and microbial community diversity. Although the effects of fertilizer application on soil microbial community and related parameters are explored, the effects on the soil microbiome associated with those of wheat plant organs, including those associated with roots and spikelets, are not well-known. Therefore, in this study, by using a sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 82 publications
3
19
0
Order By: Relevance
“… Type Factor Reference Anthropogenic Exogenous compounds (fungicide) [18] , [19] Exogenous compounds (glyphosate) [20] Exogenous compounds (insecticides) [21] Exogenous compounds (phosphine fumigation of stored wheat grains) [22] Exogenous compounds (plastic mulch film residues) [23] Fertilization [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] Inoculation of biocontrol agent [26] , [34] , [35] Land use [36] , [37] , [38] Management type [39] , [40] , [41] Overhead irrigation [42] Rotation [43] , [44] , [45] , [46] , [47] , [48] Tillage [40] , …”
Section: Factors Affecting Wheat Microbiome Structure and Diversitymentioning
confidence: 99%
See 3 more Smart Citations
“… Type Factor Reference Anthropogenic Exogenous compounds (fungicide) [18] , [19] Exogenous compounds (glyphosate) [20] Exogenous compounds (insecticides) [21] Exogenous compounds (phosphine fumigation of stored wheat grains) [22] Exogenous compounds (plastic mulch film residues) [23] Fertilization [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] Inoculation of biocontrol agent [26] , [34] , [35] Land use [36] , [37] , [38] Management type [39] , [40] , [41] Overhead irrigation [42] Rotation [43] , [44] , [45] , [46] , [47] , [48] Tillage [40] , …”
Section: Factors Affecting Wheat Microbiome Structure and Diversitymentioning
confidence: 99%
“…Members of Acidobacteria and Planctomycetes were significantly depleted in treatments receiving inorganic N and 16S rRNA gene-predicted functional structure was also impacted [27] . In another study the use of organic amendments such as biochar and manure were compared to the use of mineral fertilization on above (spikelet) and belowground (rhizosphere and root) bacterial communities, with significant changes in their structure and diversity [24] . In addition, Chen et al [25] found that nitrogen fertilization affected rhizosphere bacterial communities isolated from wheat plants during tillering but not during jointing and ripening.…”
Section: Factors Affecting Wheat Microbiome Structure and Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…The results indicated that soil enzyme activity was directly affected by the amount of fertilizer applicated. Previous studies have shown that manure application was of paramount importance to improve soil enzyme activities, which significantly increased enzyme activities more than that of chemical fertilizer application [46].…”
Section: Effect Of Different Treatments On Soil Enzyme Activitiesmentioning
confidence: 99%